1990
DOI: 10.1111/j.2042-7158.1990.tb06625.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral administration of (—)-menthol on nasal resistance to airflow and nasal sensation of airflow in subjects suffering from nasal congestion associated with the common cold

Abstract: The effects of oral administration of a lozenge containing 11 mg (-)-menthol on nasal resistance to airflow (NAR) and nasal sensation of airflow in 62 subjects suffering from nasal congestion associated with naturally acquired common cold infection have been studied. NAR was measured by posterior rhinomanometry and nasal sensation of airflow by means of a visual analogue scale (VAS). The effects of the lozenge were compared with a candy placebo lozenge in a double blind randomized trial. NAR showed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 10 publications
0
52
0
Order By: Relevance
“…In contrast, aromatic vapours (e.g. menthol) produce symptomatic relief of congestion without accompanying change in rhinomanometry measures (Eccles 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, aromatic vapours (e.g. menthol) produce symptomatic relief of congestion without accompanying change in rhinomanometry measures (Eccles 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation of menthol vapour on sucking a menthol lozenge causes a sensation of improved airflow due to a cool sensation in the nose, without any objective change in nasal airway resistance as illustrated in Figure 5 [78]. Menthol vapour can relieve symptoms of nasal congestion but is not a nasal decongestant.…”
Section: Efficacymentioning
confidence: 95%
“…Menthol is used in vaporubs, lozenges, and nasal sprays to relieve the sensation of nasal stuffiness associated with colds, and this effect is brought about by stimulation of cold receptors in the nose [77,78]. Menthol lozenges are monographed by the FDA as effective cough drops and menthol may influence cough by acting on airway sensory nerves or smooth muscle [79].…”
Section: Pharmacologymentioning
confidence: 99%
“…These factors include the thermal receptors in the vestibule and mucosa, and the mucocilliary function. Eccles et al 30 found that the nasal feeling of airflow, but not the resistance, is affected by inhaling menthol. Jones et al 31 reported a slightly increased nasal resistance, not accompanied by a corresponding feeling of obstruction, following aspirin use.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that, although the VAS has been widely used in rhinological research, [20][21][22][23][24][25][26][29][30]33 there are no studies validating this tool for assessing the subjective perception of nasal patency. Sipilä,22 in dividing the scale into quartiles, and Jose and Ell, 34 in using categorical scales, found a good correlation between rhinometric measurements and subjective data.…”
Section: Discussionmentioning
confidence: 99%